Single and binary removals of Pb(II) and Cd(II) with Chemically modified Opuntia ficus indica cladodes - Ángeles Suazo, Julio Miguel (2023)
In this study, cladodes of Opuntia ficus indica (OFIC), chemically modified with NaOH (OFICM), have been prepared, characterized, and tested as an effective biomass to remove Pb(II) and/or Cd(II) from aqueous media. At an optimum pH of 4.5, the adsorption capacity, qe, of treated OFICM was almost four times higher than that of untreated OFIC. The maximum adsorption capacities (qmax) in the single removal of Pb(II) and Cd(II) were 116.8 and 64.7 mg g−1, respectively. These values were 12.1% and 70.6% higher than those for the corresponding qmax in binary removal, which indicates the strong inhibitive effect of Pb(II) on the co-cation Cd(II) in a binary system. Structural and morphological characterization have been carried out by FTIR, SEM/EDX, and point of zero charge (pHPZC) measurements. The SEM/EDX results confirmed that the metals are adsorbed on the surface. The presence of C-O, C=O, and COO- functional groups were identified by FTIR on both OFIC and OFICM surfaces. On the other hand, we found that the adsorption processes followed the pseudo-second-order kinetics for both single and binary systems, with a fast biosorption rate of Pb(II) and Cd(II). The equilibrium data (adsorption isotherms) were better described by Langmuir and modified-Langmuir models for single and binary systems, respectively. A good regeneration of OFICM was obtained with an eluent of 0.1 M HNO3. Therefore, OFICM can be efficiently reused to remove Pb or Cd, up to three times.